Chiral recognition of macromolecules with cyclodextrins: pH- and thermosensitive copolymers from N-isopropylacrylamide and N-acryloyl-D/L-phenylalanine and their inclusion complexes with cyclodextrins - Gingter, Sabrina; Bezdushna, Ella; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2011)
In the present work we report the enantioselective recognition of water soluble stimuli-responsive polymers bearing phenylalanine moieties via host-guest interaction with β-cyclodextrin and randomly-methylated-β-cyclodextrin (RAMEB-CD). We synthesised N-acryloyl-D/L-phenylalanine monomers (2D, 2L) which were then copolymerised under free radical conditions with N-isopropylacrylamide (NIPAAm). The resulting copolymers 3D and 3L exhibit a lower critical solution temperature (LCST) of 25 °C. As a further benefit, the presence of a free carboxylic group in the copolymer system gives a high sensitivity to the pH value in respect to the LCST value. The enantioselective recognition of the side groups of copolymers 3D and 3L and their solubility behaviour were investigated by dynamic light scattering and 2D NMR spectroscopy, respectively.
Keywords: amino acid; chiral recognition; cyclodextrins; LCST; stimuli-responsive polymers

(untitled) - Zhou, J.; Ritter, H. (Polym. Chem., 2010)

(untitled) - Ohya, Y.; Takamido, S.; Nagahama, K.; Ouchi, T.; Ooya, T.; Katoono, R.; Yui, N. (Macromolecules, 2007)

(untitled) - Amajjahe, S.; Choi, S.; Munteanu, M.; Ritter, H. (Angew. Chem., Int. Ed., 2008)

(untitled) - Takashima, Y.; Osaki, M.; Harada, A. (J. Am. Chem. Soc., 2004)

(untitled) - Wenz, G.; Han, B.-H.; Müller, A. (Chem. Rev., 2006)

(untitled) - Wenz, G. (Adv. Polym. Sci., 2009)

(untitled) - Cramer, F.; Dietsche, W. (Chem. Ber., 1959)

(untitled) - Kitae, T.; Nakayama, T.; Kano, K. (J. Chem. Soc., Perkin Trans. 2, 1998)

(untitled) - Cooper, A.; MacNicol, D. D. (J. Chem. Soc., Perkin Trans. 2, 1978)

(untitled) - Alexander, J. M.; Clark, J. L.; Brett, T. J.; Stezowski, J. J. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Schurig, V. (J. Chromatogr., A, 2001)

(untitled) - Qin, L.; He, X.-W.; Li, W.-Y.; Zhang, Y.-K. (J. Chromatogr., A, 2008)

(untitled) - Liu, J.; Coffey, H.; Detlefsen, D. J.; Li, Y.; Lee, M. S. (J. Chromatogr., A, 1997)

(untitled) - Chiari, M.; Desperati, V.; Cretich, M.; Crini, G.; Janus, L.; Morcellet, M. (Electrophoresis, 1999)

(untitled) - Schwarz-Barac, S.; Ritter, H.; Schollmeyer, D. (Macromol. Rapid Commun., 2003)

(untitled) - Gingter, S.; Bezdushna, E.; Ritter, H. (Macromolecules, 2010)

(untitled) - Taguchi, K. (J. Chem. Soc., Perkin Trans. 2, 1992)

(untitled) - Choi, S. W.; Munteanu, M.; Ritter, H. (J. Polym. Res., 2009)

(untitled) - Kuwabara, T.; Takamura, M.; Matsushita, A.; Ikeda, H.; Nakamura, A.; Ueno, A.; Toda, F. (J. Org. Chem., 1998)

(untitled) - Trellenkamp, T.; Ritter, H. (Macromolecules, 2010)